Bridging the Gap between Research and Practice in Organizational Network Analysis: A Conversation between Rob Cross and Martin Kilduff. Issue 4 (26th July 2013) - Cross, Rob; Kaše, Robert; Kilduff, Martin; King, Zella; Kaše, Robert; King, Zella; Minbaeva, Dana
Abstract The article features a conversation between Rob Cross and Martin Kilduff about organizational network analysis in research and practice. It demonstrates the value of using social network perspectives in HRM. Drawing on the discussion about managing personal networks; managing the networks of others; the impact of social networking sites on perceptions of relationships; and ethical issues in organizational network analysis, we propose specific suggestions to bring social network perspectives closer to HRM researchers and practitioners and rebalance our attention to people and to their relationships.